Identification of engine inertia parameters on the basis of frequency response functions. (1st January 2012) - Xu, Chuanyan; Ding, Kang; Yang, Zhijian
Since the engine has a complicated shape and numerous attachments, the inertia parameters cannot be easily determined by purely theoretical tools. On the basis of Frequency Response Functions (FRFs) derived from vibration modal test, a residual inertia method that does not require a previous knowledge of any parameters and allows the simultaneous estimation of all the 10 engine inertia parameters is presented. The estimated method is first applied to a standard block, and the accuracy of the proposed method is evaluated through the comparison of the identified results with theoretical and LMS software estimated results. Effects on the results owing to locations and directions of the excitation and response are investigated carefully. Then, the proposed method is carried out on an engine. The estimated results are close to the results identified in LMS software and validate the effectiveness of the approach.